Environmental, Social and Governance (ESG) Disclosures in the Context of Firm Value and Financial Performance: a Conceptual Approach - Galdikaitė, Aušrinė; Budrionytė, Ramunė (Buhalterinės apskaitos teorija ir praktika, 2023)
The global practice of corporate reporting has evolved considerably over the past decades. Corporate managers have to take into account the information needs of stakeholders, which are no longer limited to the company's financial information. Non-financial information such as environmental, social and governance (ESG) disclosures are increasingly required. International organizations and governments are working together to develop ESG disclosure guidelines and standards that companies must, or can, report on ESG activities. Due to emerging ESG regulations, the integration of this non-financial information into the decision-making process is evolving into mandatory business behaviour, so it is important to understand how it can affect a firm's value and financial results. The article examines the origin of the ESG concept, methods of disclosure, motives, and the relationship between ESG and the firm's value and financial results. The results of the scientific literature analysis showed that ESG can influence the value of the company in a direct and indirect way. ESG directly affects Tobin's Q and stock prices and indirectly influences a company's value through financial performance (return on assets and equity and leverage). However, the impact does not occur in the short term due to the high implementation costs and the scale of the projects.
Keywords: firm value; financial performance; environment; social; governance